Fake Currency Verification Using Blue Pixel Region Analysis And Image Difference (International Journal of Engineering and Computer Science, 2015)
Indian paper currencies are now a days feign in various tricky techniques by the counterfeiters and is very difficult to detect. A regular bearer may easily be mislead with the note and can consider it to be a genuine one for transaction purpose. It is a very challenging job to verify an Indian currency by image processing techniques. This paper demonstrates a comparison method of colors of RGB color model on the variable color shifting property region of a genuine with that of a fake note and produces a differential comparison on abstracted regions and subsequent analysis for the validation of the procedure.